Wrist Arthrodesis With Femoral Head Structural Allograft After Failed Total Wrist Arthroplasty. Issue 3 (September 2017) - Grandizio, Louis C.; Maschke, Steven
Abstract : The failed total wrist arthroplasty represents a challenging reconstructive problem for the upper extremity surgeon. Bone loss, poor bone quality, and soft tissue defects all present technical challenges when considering revision procedures. Our purpose is to describe a technique for wrist arthrodesis after failed total wrist arthroplasty utilizing fresh-frozen femoral head allograft and dorsal plate fixation. We describe a simple method of allograft preparation for this procedure, as graft preparation and implantation can be time consuming and technically challenging.